Penggunaan Media Ropaba Untuk Meningkatkan Kemampuan Pra Membaca Anak Usia 5-6 Tahun - Najwa Nurhaifa; Aini Loita; Budi Iskandar (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Pre-reading ability is one of the basic skills that need to be developed from an early age as a provision for children to enter the next level of education. Based on the results of initial observations at Permata Hati Aisyiyah Kindergarten, the pre-reading ability of children aged 5-6 years still needs to be improved, especially in recognizing symbols and sound letters, reading simple words, and connecting letters with their sounds. This study aims to improve the pre-reading ability of children aged 5-6 years through the use of Ropaba media (Letter Wheel and Reading Board). This study uses the Classroom Action Research (CAR) method of the Kemmis and McTaggart model which is carried out in two cycles, including the stages of planning, action implementation, observation, and reflection. The research subjects were 19 children in group B2. Data collection techniques were carried out through observation and documentation, while data analysis used quantitative and qualitative descriptive techniques. The results of the study showed that the use of Ropaba media can improve children's pre-reading ability. In Cycle I, the percentage of children's pre-reading ability reached 64.21% with a sufficient category, then increased to 88.95% in Cycle II with a very good category. These improvements demonstrate that Ropaba media can create a more engaging and enjoyable learning environment, enabling children to engage more actively in learning activities. Therefore, Ropaba media can be used as an alternative learning medium to improve pre-reading skills in early childhood